2019
DOI: 10.1111/ijfs.14262
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virgin coconut oil on the physicochemical, morphological and antibacterial properties of potato starch‐based biodegradable films

Abstract: SummaryThis study investigated the effects of adding different concentrations of virgin coconut oil (VCO) on the optical, mechanical, thermodynamic and antimicrobial properties, as well as water vapour permeability and morphology of potato starch‐based biodegradable films. Increasing VCO concentrations caused a rise in the light transmittance of the films from 2.13 to 4.79 mm−1 and a decrease in water vapour transmittance from 6.77 to 2.12 (10−5 GPa−1 h−1 m−1). At a VCO concentration of 14 wt% (based on potato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 44 publications
2
19
1
1
Order By: Relevance
“…Higher content of VCO may contain a higher content of monoglyceride to transform to monolaurin derivatives and thus exert the antimicrobial effects. However, our result is contrary to a few studies reported previously [ 36 , 41 ]. Although these studies examined the film on the agar spread with Gram-negative and Gram-positive bacteria, which has the lesser contact of essential oil to the agar, but their observation shows promising antibacterial activities.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Higher content of VCO may contain a higher content of monoglyceride to transform to monolaurin derivatives and thus exert the antimicrobial effects. However, our result is contrary to a few studies reported previously [ 36 , 41 ]. Although these studies examined the film on the agar spread with Gram-negative and Gram-positive bacteria, which has the lesser contact of essential oil to the agar, but their observation shows promising antibacterial activities.…”
Section: Resultscontrasting
confidence: 99%
“…Decreased weight loss reflects the increases in the thermal behavior of a material [ 34 ]. Similar phenomena have been observed for other oil-based materials [ 35 , 36 ].…”
Section: Resultssupporting
confidence: 86%
“…Studies were carried out on many newborns under randomized controlled conditions with results showing that coconut oil has positive effects over the newborns' health and with no undesired side effects [6,69]. Studies are also being conducted on the feasibility of using coconut oil to synthesis edible packaging material as an additive for starch-based films in food packaging as an enhanced edible film [70][71][72]. Further extraction of virgin coconut oil can be carried out to obtain medium-chained triglyceride, which was found to be a major component of coconut oil [73].…”
Section: Industrial Applicationsmentioning
confidence: 99%
“…The mechanism of lauric acid antimicrobial function may include the degradation of cell walls, cell signals, and transcription interference. The virgin CO has bacterial inhibition effect on Staphylococcus aureus , Listeria monocytogenes , and Escherichia coli and also has an impact on the mechanical and water barrier properties of edible films 22–25 …”
Section: Introductionmentioning
confidence: 99%